Deskripsi Pengelolaan Emosi Pada Anak Usia Dini di Tk Islam Az-Zahra Kota Gorontalo - Putri M Halim; Agustina Ngabito; Salsabilla Tri Febrianti.b; Nena Pratiwi Bone; Amelia Alfiaty (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe emotional management in early childhood at Az-Zahra Islamic Kindergarten. Emotional management is a fundamental ability that needs to be developed early on to support children's social, cognitive, and academic development. The study used a qualitative approach with a descriptive method. The subjects of the study were children aged four to six years at Az-Zahra Islamic Kindergarten with a total of thirty students. Data collection techniques used observation, interviews, and documentation. The results of the study showed that emotional management at Az-Zahra Islamic Kindergarten was carried out through various strategies such as storytelling activities, role-playing, habituation of dhikr and prayer, and direct guidance from teachers. The implementation of Islamic values ​​in emotional management has a positive impact on children's ability to control and express emotions appropriately. This study concludes that a holistic approach that integrates Islamic values ​​with modern pedagogical strategies is effective in developing emotional management skills in early childhood.